Portal‐Vein Compression Caused by Double‐Pigtail Plastic Biliary Stent - Shinsuke Akiyama; Masaya Wada; Tetsuro Inokuma (JGH Open)
ABSTRACT Introduction Reports of pseudoaneurysms associated with biliary self‐expandable metallic stent (SEMS) placement have been increasing. Recently, cases of hepatic pseudoaneurysm rupture caused by double pigtail plastic stents (DPS) have also been reported. The symptoms of pseudoaneurysms are often non‐specific, and many cases are diagnosed only after rupture. Therefore, early detection and appropriate treatment are required. Case Presentation A 45‐year‐old woman presented with obstructive jaundice caused by pancreatic head cancer, with imaging revealing common bile duct stenosis and intrahepatic bile duct dilation. Endoscopic retrograde cholangiopancreatography (ERCP) was performed to place a DPS in the left hepatic duct, relieving jaundice. However, follow‐up contrast‐enhanced computed tomography (CE‐CT) revealed differences in arterial‐phase blood flow between the liver lobes without reduction in portal vein blood flow. Therefore, the compression and stenosis of the left branch of the portal vein caused by the DPS were clearly identified using three‐dimensional computed tomography (3D‐CT). The DPS was replaced with a straight‐type stent, preventing further complications. The patient subsequently underwent successful pancreaticoduodenectomy without any surgical complications. Conclusion This is a case of portal vein compression caused by double‐pigtail plastic biliary stent. By promptly recognizing the differences in arterial‐phase blood flow between the liver lobes and replacing the DPS with a straight‐type plastic stent, complications, such as portal vein pseudoaneurysm formation, rupture, embolism, or thrombosis, were successfully avoided.